A novel Meloidogyne enterolobii effector MeTCTP promotes parasitism by suppressing programmed cell death in host plants. (12th April 2016) - Zhuo, Kan; Chen, Jiansong; Lin, Borong; Wang, Jing; Sun, Fengxia; Hu, Lili; Liao, Jinling
Summary: Meloidogyne enterolobii is one of the most important plant‐parasitic nematodes that can overcome the Mi‐1 resistance gene and damage many economically important crops. Translationally controlled tumour protein (TCTP) is a multifunctional protein that exists in various eukaryotes and plays an important role in parasitism. In this study, a novel M. enterolobii TCTP effector, named MeTCTP, was identified and functionally characterized. MeTCTP was specifically expressed within the dorsal gland and was up‐regulated during M. enterolobii parasitism. Transient expression of MeTCTP in protoplasts from tomato roots showed that MeTCTP was localized in the cytoplasm of the host cells. Transgenic Arabidopsis thaliana plants overexpressing MeTCTP were more susceptible to M. enterolobii infection than wild‐type plants in a dose‐dependent manner. By contrast, in planta RNA interference (RNAi) targeting MeTCTP suppressed the expression of MeTCTP in infecting nematodes and attenuated their parasitism. Furthermore, MeTCTP could suppress programmed cell death triggered by the pro‐apoptotic protein BAX. These results demonstrate that MeTCTP is a novel plant‐parasitic nematode effector that promotes parasitism, probably by suppressing programmed cell death in host plants.